2016
DOI: 10.1073/pnas.1615322113
|View full text |Cite
|
Sign up to set email alerts
|

Nogo receptor blockade overcomes remyelination failure after white matter stroke and stimulates functional recovery in aged mice

Abstract: White matter stroke is a distinct stroke subtype, accounting for up to 25% of stroke and constituting the second leading cause of dementia. The biology of possible tissue repair after white matter stroke has not been determined. In a mouse stroke model, white matter ischemia causes focal damage and adjacent areas of axonal myelin disruption and gliosis. In these areas of only partial damage, local white matter progenitors respond to injury, as oligodendrocyte progenitors (OPCs) proliferate. However, OPCs fail … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
124
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(131 citation statements)
references
References 61 publications
(80 reference statements)
7
124
0
Order By: Relevance
“…Gpr17 was previously found to be expressed in OPCs and premature oligodendrocytes (Fumagalli et al, 2011), and it has been proposed to have a role in OPC differentiation and developmental myelination (Chen et al, 2009;Simon et al, 2016;Viganò et al, 2016). These studies showed that Gpr17 inhibits OPC differentiation in vitro and delays myelination during development in vivo.…”
Section: Review Of Ou Et Almentioning
confidence: 92%
See 4 more Smart Citations
“…Gpr17 was previously found to be expressed in OPCs and premature oligodendrocytes (Fumagalli et al, 2011), and it has been proposed to have a role in OPC differentiation and developmental myelination (Chen et al, 2009;Simon et al, 2016;Viganò et al, 2016). These studies showed that Gpr17 inhibits OPC differentiation in vitro and delays myelination during development in vivo.…”
Section: Review Of Ou Et Almentioning
confidence: 92%
“…A first step toward developing potential promyelinating therapies is to identify genes whose expression is affected during demyelination and subsequent remyelination. Ou et al (2016) used this approach and reported their findings in a study recently published in The Journal of Neuroscience.…”
Section: Review Of Ou Et Almentioning
confidence: 99%
See 3 more Smart Citations